2019
DOI: 10.1111/jonm.12874
|View full text |Cite
|
Sign up to set email alerts
|

Experiences and outcomes of nurses referred to a peer health assistance program: Recommendations for nursing management

Abstract: Aim To provide recommendations for nursing management based on the experiences of current and former nurses who were served by a peer health assistance program (PHAP). Background Providing help for nurses with impaired practice is critical to their health and well‐being, assuring patient safety and public trust, as well as returning competent nurses to the healthcare workforce. Methods Nurses (n = 268) who were current clients or former clients of a PHAP were surveyed about their experiences. Results Nearly ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 12 publications
1
30
0
Order By: Relevance
“…Seven of the nine articles on recovery and monitoring programs described nurses' experiences of recovering from SUD with the support of ADPs (Bowen et al, 2012; Cares et al, 2015; Clark & Farnsworth, 2006; Dittman, 2008; Horton-Deutsch et al, 2011; McNelis et al, 2012; Pace et al, 2020). One article compared the accessibility and benefits of alternative and discipline-based programs (Monroe et al, 2013), and one described the benefits of both types of program from the perspective of nurses (Fogger & McGuinness, 2009; see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Seven of the nine articles on recovery and monitoring programs described nurses' experiences of recovering from SUD with the support of ADPs (Bowen et al, 2012; Cares et al, 2015; Clark & Farnsworth, 2006; Dittman, 2008; Horton-Deutsch et al, 2011; McNelis et al, 2012; Pace et al, 2020). One article compared the accessibility and benefits of alternative and discipline-based programs (Monroe et al, 2013), and one described the benefits of both types of program from the perspective of nurses (Fogger & McGuinness, 2009; see Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Peer health assistant programs (PHAP), developed decades ago as alternatives and/or adjunctive to state regulatory discipline are offered in some states to support nurses with substance use and mental health issues ( National Council of State Boards of Nursing, 2019 ). These appear insufficient as Pace et al (2020) reported barriers to help-seeking among nurses who were current or former clients of a PHAP. The programs are often not used because fear, embarrassment, and concerns about losing one's nursing license inhibits contact.…”
Section: Drivers Of Suicide In Nursingmentioning
confidence: 95%
“…Using a strategic planning process, 40 41 with modifications for nursing-specific strategies. 11,25,45,46…”
Section: An Approach To Moving Forwardmentioning
confidence: 99%
“…Peer support programs can be structured within a health care system, offered as an extension of alternative to discipline programs, be a freestanding program, or be available individually with the utilization of telehealth and nurse coaching. 46,47 Nursing leadership plays an important role in increasing access to services, raising awareness through education, integrating peer support language to relevant policies (ie, reasonable suspicion of impairment), and encouraging earlier compassionate intervention without fear of immediate termination for mental health or substance use disorder. 46 Implementing internal programs or referring to external peer support resources benefits individual nurses and systems by promoting a culture of awareness, compassion, and help-seeking behaviors.…”
Section: Peer Supportmentioning
confidence: 99%